1983
DOI: 10.1111/j.1600-0447.1983.tb06739.x
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone suppression test and TRH test in endogenous depression

Abstract: Dexamethasone suppression test (DST) and thyrotropin releasing hormone (TRH) stimulation test were performed in 34 patients with endogenous depression. Compared with 33 psychiatric controls (limit of discrimination for serum cortisol of 275 nmol/l = 10 micrograms/100 ml) the specificity of the DST was 91% and the sensitivity was 65%. Compared with 24 healthy subjects the sensitivity of the TRH test was 24%, and the combined sensitivity for the DST and the TRH test was 76%. In contrast to the TRH test the DST s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0
1

Year Published

1985
1985
1989
1989

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(10 citation statements)
references
References 12 publications
1
8
0
1
Order By: Relevance
“…These findings are in accordance with those of other authors [Holsboer et al, 1982;Aggernaes et al, 1983;Maes et al, 1986aMaes et al, , b, 1987, Also, we found a significant relation between age and the postdexamethasone values at 8 a.m. However only 2.2% of the variance in the DST results could be explained by age effects.…”
Section: Discussionsupporting
confidence: 83%
“…These findings are in accordance with those of other authors [Holsboer et al, 1982;Aggernaes et al, 1983;Maes et al, 1986aMaes et al, , b, 1987, Also, we found a significant relation between age and the postdexamethasone values at 8 a.m. However only 2.2% of the variance in the DST results could be explained by age effects.…”
Section: Discussionsupporting
confidence: 83%
“…Others have focused on abnormalities in the self-regulation of catecholaminergic systems in the case of thyroid dysfunction (35). Some studies have found hypothyroidism, either clinical or subclinical, in some rapid cycling affective patients (18,(120)(121)(122)(123)126). Some studies have found hypothyroidism, either clinical or subclinical, in some rapid cycling affective patients (18,(120)(121)(122)(123)126).…”
Section: Suggested Mechanisms Of Actionmentioning
confidence: 99%
“…Several hypotheses have been suggested to explain the stabilizing effect of thyroid hormones on rapid cycling, but the exact mechanism still remains obscure (1 18,131). Some have associated the deficiency of thyroid hormones with dysfunction in the periodicity of various biological rhythms responsible for the stabilization of mood (1 18).…”
Section: Suggested Mechanisms Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…A proportion (35 to 60 per cent) of patients with major depression show a disturbed DST (1)(2)(3)(4)(8)(9)(10). Some authors have found that patients with major depression exhibit a disturbed MHPG excretion (11)(12).…”
mentioning
confidence: 97%